Semiotic Analysis of 'Kun Fa Yakoon' Song Using Riffaterre’s Theory - Choironi, Merry; Ahmad, Lalu Turjiman; Saber, Ahmad Autiyah (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article tried to find out the hidden meaning in the song Kun Fa Yakoon, written by Mohammad bin Dhahi, one of the most popular songs in the Muslim world during the pandemic Covid-19, not only due to the imitation of one of the current most popular Western songs, Memories by Maroon, but the acapella is also interesting due to the overwhelming symbols within the lyrics. Thus, new meanings need to produce to comprehend the song and its cultural context. This article aimed to deepen the comprehension of the song's message to result in an increased appreciation for art and a better understanding of the circumstances during the difficult times of the pandemic. The type of research conducted is qualitative research. In analysis, researchers used Riffaterre's Semiotics theory by identifying the Semiotic elements of the song, such as the use of metaphors and repetitions, then conducting heuristic reading and interpretation, and producing meaning through hermeneutic reading. The research findings indicate the discovery of meaning shifts in the form of metaphors and the creation of meaning through repetitions. In the heuristic analysis, ungrammatical elements like